Experimental Study on Compression and Intrinsic Permeability Characteristics of Municipal Solid Waste - Gang Zeng; Jun Ma; Dan Hu; Jing Wang (Advances in Civil Engineering)
Compression and gas permeability characteristics of municipal solid waste (MSW) are of great significance to the design, construction, management, and operation of landfill. The objective of this paper was to study the compression and gas permeability characteristics of MSW. A compressing test device and gas permeability test device for MSW were introduced, and laboratory tests were carried out. The test results showed that the final strains at the vertical loads of 100 kPa, 200 kPa, 300 kPa, and 400 kPa were 35.8%, 45.1%, 49.2%, and 55.1%, respectively. The natural logarithm of void ratio and pressure was linearly correlated at different times. Intrinsic permeability measured without considering gas compressibility was smaller than that measured with considering gas compressibility. Intrinsic permeability of MSW decreased with the increase of the inlet pressure. It was suggested that the inlet pressure should be set to 3 kPa for the indoor gas permeability test of MSW. Intrinsic permeability of MSW decreases with the increase of water content and compression displacement. Power function and logarithmic model were suitable for the fitting of permeability and porosity of manually prepared fresh MSW samples, while the K-C model was not suitable. With the increase of moisture content, the coefficient and power index of the power function model decreased gradually. And the slope and intercept of the double logarithmic model also decreased gradually with the increase of moisture content.